They both die at the end - Silvera, Adam 1990- (New York [United States] Harper Teen, an imprint of HarperCollinsPublishers, 2018)
In a near-future New York City where a service alerts people on the day they will die, teenagers Mateo Torrez and Rufus Emeterio meet using the Last Friend app and are faced with the challenge of living a lifetime on their End Day
Keywords: Death -- Fiction; Friendship -- Fiction; Love -- Fiction